Nationhood and loyalty in Islam: Between Dustur al-Madinah and the Bukit Seguntang Covenant - Din, Fadzilah; Abdul Jalil, Mohd. Noh (2017)
This paper aims at analyzing the concept of nationhood in Islam as enshrined in the Dustur al-Madinah or Charter of Medina which is the first state constitution in Islam. The first state governed by the Muslims in Madinah under the leadership of Prophet Muhammad (peace be upon him) provides clearer understanding of Quranic injunctions on nationhood in Islam. The Dustur al-Madinah introduced by the Prophet illustrates the rights and responsibilities of all citizens including the non-Muslims living under the Muslim leadership in Madinah. In light of this, a study of the Dustur would be the main discussion in this paper. In addition, a close look into the first covenant between the Malays and their ruler in the Bukit Seguntang Covenant also shed further understanding on the concept of nationhood and loyalty during the early period of Islam in the Malay world. This paper concludes that Dustur al-Madinah highlights a living example not alien to the concept of modern nationhood and loyalty in the modern times while the Bukit Seguntang Covenant provides the Malays traditional understanding of nationhood and loyalty. According to the Dustur, the mercy of Islam is meant for all human beings regardless of their beliefs, ethnicity, traditions and other diversities, whereas the Bukit Seguntang Covenant relates similar Malay values in its traditional context. However, the principle and values of both documents are similar in nature and are not contradictory. Thus they are applicable to modern living if followed properly. The incongruent practices today that are against the principles mentioned in the Dustur al-Madinah committed by Muslims under the name of Islam are not representing the Islamic teachings but simply a distortion of Islamic teaching that can be found in the Qur’an and the practice of the Prophet, nor do they tally with the principle of concept of loyalty portrayed in Bukit Seguntang Covenant.